PENINGKATAN KUALITAS HAFALAN DAN PEMAHAMAN AL-QUR’AN SANTRI MENGGUNAKAN METODE HQ4T - Hasiolan Alan; MHD Rozali; Nikmawati (EL-ADABI : Jurnal Studi Islam, 2024)
The purpose of this article is to see how the role of the HQ4T method in improving the quality of memorization and understanding of the Qur'an for students. Memorizing the Qur'an has its appeal in post-modern society, even surpassing the number of Qur'an memorizers in Saudi Arabia. However, the quantity is not in harmony with the quality because many students only get the predicate of memorization but are not able to read everything by rote in bi al-qaib (reading without looking at the mushaf). In another fact, many students only focus on increasing the number of memorization but do not improve the quality of comprehension. Even though the Qur'an is a book of instructions, not a book of memorization. To answer this problem, the researcher uses a qualitative research method that is descriptive with the analysis of the HQ4T method. The results of the study showed that the improvement in the quality of students' memorization was seen in the ability of students to immediately recall the verses that had been memorized when needed. Meanwhile, the increase in understanding can be seen in the ability of students to rewrite and translate each verse that has been memorized.